STRATEGI PENGELOLAAN PROGRAM TAHFIDZ AL-QUR’AN BERBASIS DIFERENSIASI KEMAMPUAN SISWA DI MA MA’ARIF NU ASSA’ADAH GRESIK - Ririn Inayatul Mahfudloh; Khoiril Waroh (MPI STAI Sangatta Kutai Timur, 2026)
This study aims to analyze the management strategies of a Qur’anic tahfidz program based on students’ differentiated abilities, including program implementation, teachers’ pedagogical strategies, and the supporting and inhibiting factors in its implementation. The study employed a qualitative approach with a descriptive-analytical design. Data were collected through observation, in-depth interviews with tahfidz teachers and madrasah administrators, as well as documentation of learning activities. Data analysis was conducted thematically through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the management strategies of the differentiated tahfidz program were implemented through diagnostic assessments to identify students’ initial abilities, flexible grouping based on ability levels, adjustment of memorization targets, and the development of adaptive teaching methods and instructional media. Teachers’ pedagogical strategies included the use of talaqqī, tikrār, peer tutoring, audio and visual learning media, immediate feedback, and the reinforcement of spiritual motivation. This approach was found to improve student engagement, the quality of Qur’anic recitation, memorization consistency, and learners’ self-confidence. Supporting factors included teacher competence, student motivation, parental involvement, the availability of learning facilities, and institutional policies that support the tahfidz program. Meanwhile, inhibiting factors consisted of limited instructional time, imbalanced teacher-student ratios, and the uneven understanding of differentiated instruction among teachers. The study concludes that differentiated management strategies in Qur’anic tahfidz programs constitute an effective approach to accommodating students’ diverse abilities and contribute significantly to improving the academic and spiritual quality of tahfidz learning.